Hard and soft X‐ray photoelectron spectroscopy for selective probing of surface and bulk chemical compositions in a perovskite‐type Ni catalyst. (29th June 2020) - Sambalova, Olga; Billeter, Emanuel; Mann, Jennifer; Miyayama, Takuya; Burnat, Dariusz; Heel, Andre; Bleiner, Davide; Borgschulte, Andreas
Abstract : Combined chemical analyses of both the surface and bulk of industrial catalysts is a significant challenge, because all microanalysis methods reveal either the surface or the bulk properties but not both. We demonstrate the combined use of hard and soft X‐ray photoelectron spectroscopy (XPS) as a powerful, practical, and nondestructive tool to quantitatively analyze the chemical composition at the surfaces (~1 nm) and subsurfaces/bulk (~10 nm) for catalysts. The surface‐bulk differentiation is achieved via an exchangeable anode system, where the Al (Kα, 1486.6 eV) and Cr (Kα, 5414.7 eV) for the XPS and hard X‐ray photoelectron spectroscopy (HAXPES) analyses, respectively, are interchanged without affecting the X‐ray beam position on the sample. As an archetypical catalyst, we study the perovskite‐type material La0.30 Sr0.55 Ti0.95 Ni0.05 O3‐δ (LSTNO), which has differing chemical compositions at the surface and subsurface after reduction and oxidation reactions. We look at the relative changes in surface composition, which minimizes the error stemming from the differing relative sensitivity factors in the oxidized and reduced states. The HAXPES‐XPS analysis indirectly confirms the well‐known exsolution and formation of Ni nanoparticles on the surface upon reduction though following changes of Ni concentration at the surface. However, the XPS‐HAXPES analysis demonstrates an increase in not only the Ni but also the Sr, which corroborates the reorganization within the perovskite lattice upon reduction. The XPS‐measured intensities decrease for all the accessible peaks (La 3d, Sr 3d, lattice O 1s, and Ti 2p), which is attributed to the photon diffusion by the surface Ni nanoparticles.